KESIAPAN GURU BAHASA INDONESIA SMP DALAM IMPLEMENTASI KURIKULUM 2013 - Pujiono, Setyawan (LITERA, 2014)
This study aims to describe the readiness of teachers at junior high schools (JHSs) in the implementation of Curriculum 2013. The readiness comprises their understanding of the curriculum and abilities to prepare learning kits, design the syllabus, and develop learning materials. This was a descriptive study employing the survey approach. The research subjects were Indonesian language teachers at JHSs in Kulonprogo Regency. The data were collected through a questionnaire and were descriptively analyzed using categories based on each characteristic. The results show that Indonesian language teachers at JHSs are ready to implement Curriculum 2013. This is indicated by: (1) their understanding of the curriculum contents (68.91%), (2) their readiness in lesson planning (68.69%), (3) their readiness in learning implementation (72.67%), and (4) their understanding of evaluation and learning mastery (67.83%). The improvement of the readiness in the implementation of Curriculum 2013 is made through intensifying socialization, enriching supplementary materials, and attending training on lesson plan designs.